Pengaruh Technology Acceptance Model terhadap Penggunaan e-Filing (Studi pada Wajib Pajak Orang Pribadi di KPP Pratama Singaraja) - Kadek Dwi Andika; I Nyoman Putra Yasa (Universitas Pendidikan Ganesha, 2020)
This study aims at examining the effect of the Technology Acceptance Model towards the used of e-filing (research on individual taxpayers at Singaraja KPP). The data used in the form of primary data obtained from questionnaires. The sample used is an individual taxpayer who uses e-filing registered at Singaraja Pratama Tax Service Office. The subject of this study were 344 individual taxpayers. This study used purposive sampling. The data analysis technique of this study is multiple regression testing using the SPSS program. The results showed that the perception of usefulness, perceived convenience, and perceived readiness of information technology affect the use of e-filing in Singaraja.